Determinan Pemanfaatan Jamban Keluarga pada Keluarga - Puji Eka Mathofani; Annissa Annissa; Rika Prastiwi Metalia (Faletehan Health Journal, 2020)
Latrines are one of the basic human needs, it is expected that each individual uses the toilet facilities for defecation. Based on data from the Cipanas Inpatient Health Center as many as 1,502 people have access to 4,237 latrines. This study aims to determine the factors associated with the use of family latrines in the Cipanas Village Cipanas Inpatient Health Work Area Cipanas District Lebak Regency in 2019. The research design is cross-sectional. The study population was all family heads in Cipanas Village, amounting to 1.158 families with a sample of 101 households, where the sample was taken by a simple random sampling method. Primary data collection using questionnaires by interview, while secondary data were obtained from the Cipanas Health Center. Analysis results showed that out of 101 respondents 45.4% did not use latrines, 82.2% had high incomes, 58.4% had poor attitudes, 62.4% did not have latrines, 71.3% had the role of health workers, and 61.4% had community leaders. The correlation analysis shows that there is a significant relationship between attitudes, latrine ownership, the role of health workers (Pv = 0.000), the role of community leaders (Pv = 0.005) and the use of family latrines. Suggestions for this research are the need to increase the knowledge and awareness of family heads in the use of family latrines.